Original paperBIAS OF JUDGING IN MEN’S ARTISTIC GYMNASTICS AT THE EUROPEAN CHAMPIONSHIP 2011 - Leskošek, B.; Čuk, I.; Pajek, J.; Forbes, W.; Bučar-Pajek, M. (Biology of Sport, 2012)
The purpose of this study was to establish the validity (unbiasedness) and reliability of E-panel judges officiating execution of exercises in men’s artistic gymnastics at the European Championship 2011 (EC 2011) in Berlin. Overall bias was established in terms of average over-scoring or under-scoring of each judge compared to the final E score of a judges’ E panel. National bias was expressed as average over-scoring of gymnasts of the same nationality as the judge’s. Both types of bias were mostly small (within the +/- 0.1 point range), but statistically significant and also substantial (over 0.2 point) in some cases. Compared to other competitions, it seems that bias is becoming smaller over time and is also smaller in competitions of higher importance. Analysis of possible consequences of bias showed that overall bias may influence both scores and ranks of competitors, while national bias may be especially problematic in the qualification round, where it may prevent some competitors from qualifying for apparatus finals.